Implantação de tecnologia de monitoramento remoto para e-service: um estudo exploratório - Jacinto, Marcos Fernando Fontura dos Santos (2002)
The purpose of this study is to define measures to increase customer satisfaction and company competitiveness using a remote monitoring technology, in an exploratory study of Alpha Elevator Company (nick name chosen to the company by the actor of the dissertation). Regarding the competitive market, the service industry is striving to achieve productivity, following the example of the manufacturing industry. Nevertheless, these efforts are limited by the amount of hours worked per week, month or year, since the sector charges its services based on the hours spent working on the equipment of the client or based on the numbers of visits. This study is based in the overcoming of the traditional paradigm of selling number of hours by a system of selling results and performance. Employing a remote monitoring system, the elevators under the company service are monitored continually and defects are detected and transmitted to the customer care center, via phone line. The customers can access this data through the Internet and obtain information like availability rate of their elevators and call back response time rate, besides being able to buy products on the company¿s home page and to send feedback. The results were obtained by participating in conferences among experts of the company, in Japan and the United States. Through the analysis of the business environment and based on the bibliographic reference, a strategy was developed to implement e-service as a competitive differentiation.